Incoming tour operators perspectives in a highly competitive environment - case of Slovakia - Fodranová, Iveta; Puškelová, Mária; Mrkvová, Katarína; Dudić, Branislav (Hotel and Tourism Management, 2019)
Tour operators play a central role in the tourism industry. For tourism distribution channels, the emergence of new ones has been of particular significance, since it leads to priorities change in terms of distribution. The purpose of the current study was to examine the Slovak incoming tour operators in relation to tourism distribution in a highly competitive environment. The findings show that the Slovak incoming tour operators as a mediator of accommodation services are not the first choice of a foreign customer when it comes to accommodation provision. This is the consequence of the fact that tour operators are not able to compete in an adequate way with electronics distribution channels (e.g. Booking, Trivago, Go global and others). The research results show that the Slovak incoming tour operators are not able to develop their activities concerning booking offer. If they want to survive, they will have to change their traditional business model and structure their product portfolio and focus on offer of new different services and dynamic products.